2018
DOI: 10.1007/s00464-018-6284-z
|View full text |Cite
|
Sign up to set email alerts
|

Towards spill-free in-bag morcellation: a health failure mode and effects analysis

Abstract: BackgroundTo assess potential risks of new surgical procedures and devices before their introduction into daily practice, a prospective risk inventory (PRI) is a required step. This study assesses the applicability of the Health Failure Mode and Effects Analysis (HFMEA) as part of a PRI of new technology in minimally invasive gynecologic surgery.MethodsA reference case was defined of a patient with presumed benign leiomyoma undergoing a laparoscopic hysterectomy or myomectomy including in-bag power morcellatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…But even using these tools, accidental morcellation of early uLMS tumors (stage Ia with a diameter of less than 5 cm confined to the uterus) may not be avoided, and stage Ia is the best prognostic group in uLMS. Therefore attention should be payed to risk analysis of endoscopic in-bag procedures [47] in order to improve safety by means of appropriate tools and operation procedure pathways for patients outside a score-defined risk population.…”
Section: Analysis Of Case Report and Discussionmentioning
confidence: 99%
“…But even using these tools, accidental morcellation of early uLMS tumors (stage Ia with a diameter of less than 5 cm confined to the uterus) may not be avoided, and stage Ia is the best prognostic group in uLMS. Therefore attention should be payed to risk analysis of endoscopic in-bag procedures [47] in order to improve safety by means of appropriate tools and operation procedure pathways for patients outside a score-defined risk population.…”
Section: Analysis Of Case Report and Discussionmentioning
confidence: 99%
“…Evaluation of the HFMEA has shown that although it is a time-and resource-intensive method, it is useful for assessing and improving the safety of healthcare processes [30][31][32]. The HFMEA has proven successful for improving patient safety in processes such as blood transfusions, drug administration, and in the introduction of new surgical techniques [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a cautious manipulation of the tumor, bags and instruments minimizes the risk of intraoperative spillage, especially in cases of larger myomata. Moreover, there is a lack of evidence regarding how much of a bag puncture would provoke tissue spillage, as well as the meaning of micro-spillage occurring in inadvertent breach of bag integrity [ 25 ]. In the presented case no tissue spillage or bag puncture occurred.…”
Section: Discussionmentioning
confidence: 99%